Impact of Carbon Properties on Mo2C/Carbon Catalysts for the Hydrodeoxygenation of 4-Methylphenol - Liu, Shida; Wang, Haiyan; Putra, Robertus Dhimas Dhewangga; Kim, Chang Soo; Smith, Kevin J. (American Chemical Society, 2019)
Petcoke and biochar were chemically activated with KOH at 800 and 700 degrees C, respectively, to obtain microporous activated petcoke (APC) and activated biochar (ABC) with large surface areas (similar to 2000 m(2)/g). The O content of the petcoke increased, whereas that of the biochar decreased following activation. Nevertheless, ABC had a higher O content on the surface and in the bulk compared to APC. APC and ABC precursors were wet impregnated with ammonium heptamolybdate, dried, and reduced in H-2 to yield Mo2C/APC and Mo2C/ABC catalysts with a nominal loading of 10 wt % Mo. These catalysts were assessed for the hydrodeoxygenation (HDO) of 4-methylphenol. The Mo2C/ABC catalyst had higher activity (per gram Mo) and direct deoxygenation selectivity than the Mo2C/APC because of the higher dispersion of Mo species and higher O content on the ABC surface. The 10%Mo2C/ABC_R650 catalyst prepared at carbothermal hydrogen reduction of 650 degrees C had the highest activity per gram Mo among all catalysts, whereas turnover frequencies on all catalysts were similar.